THE ROLE OF MOTIVATION IN TEACHING LANGUAGE. - Turg'unova Hilolaxon Anvarjon qizi (TADQIQOTLAR.UZ, 2024)
Annotation: This article explores the pivotal role of motivation in the teaching and learning of languages. It delves into different motivational theories, the impact of intrinsic and extrinsic motivation on language acquisition, and practical methods to enhance student motivation. Through literature analysis and empirical data, the study aims to provide educators with insights and strategies to foster a more motivating learning environment.